Enrichment and remediation of uranium by microorganisms: A review - Qiuhan Yu; Ouyang Cui (Open Journal of Environmental Biology - Peertechz Publications, 2023)
Uranium is a key raw material for the nuclear energy industry, the generation of nuclear energy is projected to double by 2040 to address the growing energy demands, which makes the uranium supply a matter of energy security. In addition, uranium is a heavy metal with both chemotoxicity and radiotoxicity, which seriously endangers human health and environmental safety. The growth in the utilization of uranium resources boosts the release of uranium into the environment. Therefore, the remediation of uranium contamination and recovery of uranium from a non-conventional approach is highly needed. Microorganism exhibits a high potential for immobilization of uranium. This review summarizes the ability of microorganisms to immobilize uranium from aqueous solutions and wastewater in terms of microbial species, performance, mechanism of enrichment and remediation, and applicable environment.